Impact of preadmission anti‐inflammatory drug use on the risk of RBC transfusion in elderly hip fracture patients: a Danish nationwide cohort study, 2005–2016. Issue 3 (4th January 2019) - Glassou, Eva N.; Kristensen, Nickolaj; Møller, Bjarne K.; Erikstrup, Christian; Hansen, Torben B.; Pedersen, Alma B.
Abstract : BACKGROUND: Do prescription drugs with anti‐inflammatory properties such as nonsteroidal anti‐inflammatory drugs (NSAIDs), corticosteroids, and statins increase the risk of postoperative bleeding measured with RBC transfusion in elderly hip fracture surgery patients? STUDY DESIGN AND METHODS: Using the Danish Multidisciplinary Hip Fracture Database, 74, 791 patients aged 65 years or older with surgery‐treated hip fracture were identified during 2005–2016, and their use of NSAIDs, corticosteroids, and statins was ascertained. For each drug, patients were categorized as nonusers (no prescription ≤365 days prior to surgery), former users (one prescription 91–365 days), and current users (one prescription ≤90 days). Information on surgical treatment, transfusion, other medication and comorbidities were collected using Danish nationwide registries. A log‐binomial model was used to estimate relative risks for RBC transfusion within 7 days of surgery and corresponding 95% confidence intervals. Adjustments were made for patient‐ and surgery‐related factors. RESULTS: Former and current users of NSAIDs, corticosteroids, and statins accounted for 22%, 10%, and 24%, respectively. Current users of NSAIDs had an increased adjusted relative risk of transfusion (1.07; confidence interval, 1.04–1.10) compared to nonusers. There was no association between current users of corticosteroids and statins and risk of transfusion. CONCLUSION: NSAID use within 90 days of a hip fracture surgery was associated with an increased risk of RBC transfusion. Thus, current use of NSAIDs can be associated with an increased risk of postoperative bleeding, but we cannot rule out the influence of confounding.